Economic and social well-being from the perspective of Islamic economics – a conducted study on Erbil Governorate for the year 1443 AH / 2022 AD (Raparin Journal of Humanities (RJH), 2023)
According to Islamic economics، achieving economic and social well-being entails creating a society based on righteousness and piety that is interdependent، cooperative، and has a high standard of living for its citizens. This is what we see in Islamic societies and throughout different Islamic historical periods، as long as Zakat(Alms )، which is the primary driver of prosperity in this study، continues to eradicate poverty، affliction، and drudgery. Alms، is viewed as a continual financial and living guarantee for every Muslim person and his economic and social well-being through all changes in time، place، and current being. Alms (Zakah) expenditures are only for the poor and for the needy and for those employed to collect [zakah] and for bringing hearts together [for Islam] and for freeing captives [or slaves] and for those in debt and for the cause of Allah and for the [stranded] traveler - an obligation [imposed] by Allah. And Allah is Knowing and Wise)At-Tawbah-60: